(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To assess the analgesic effects and improvement in cervical spine mobility achieved by Jin’s three - needle technique combined with acupressure massage in patients with cervical scapulohumeral syndrome resulting from cervical disc herniation. Methods: This study employed a controlled clinical trial, comparing outcomes before and after treatment with a control group. A total of 60 patients were divided into two groups: the study group received Jin’s three - needle technique combined with acupressure massage, while the control group received electroacupuncture combined with acupressure massage. Results: After 14 days of treatment, the mean Visual Analog Scale (VAS) score in the study group decreased significantly from 5.07 ± 0.74 (points) to 2.87 ± 1 (points) (p < 0.01); with an observed improvement in cervical spine range of motion (p > 0.05). No statistically significant differences were found between the two groups (p > 0.05). Conclusion: Jin’s three - needle technique, when combined with acupressure massage, demonstrates effective pain relief and improvement in cervical spine mobility in patients with cervical scapulohumeral syndrome caused by cervical disc herniation. However, there were no statistically significant differences between the two groups (p > 0.05).